The impact of coronavirus 2019 on general surgery residency: A national survey of program directors - Kilcoyne, Maxwell F. (Ann Med Surg (Lond), 2021)
BACKGROUND: Coronavirus disease 2019 (COVID-19) has had a widespread impact on graduate medical education. This survey aims to assess how general surgery residency programs adapted to the initial wave of the COVID-19 pandemic in the United States (US). MATERIALS AND METHODS: General surgery program directors (PDs) in the US were invited to partake in a 16-question survey between April 17 and May 1, 2020. The survey included questions about basic program information, clinical practice changes, changes to education structure, surgery resident clinical duties, and perceived impact on resident operative experience and future career choices. RESULTS: Forty-eight PDs completed the survey in the designated two-week period. Almost all (44/48, 91.7%) programs changed their didactic education to an online video conference-based format. Thirteen programs (27.1%) decreased the amount/frequency of formal education, and 13 (27.1%) reported canceling didactic education for some period of time. The majority of PDs (26/48, 54.2%) felt these changes had no impact on resident didactic participation, 14 (29.2%) reported an increase in participation, and 8 (16.7%) reported decreased participation. Ten programs (20.8%) redeployed residents to non-surgical services at the time of this survey, 30 (62.5%) have not redeployed residents but plan to if needed, and 8 (16.7%) did not have any plans to redeploy residents. CONCLUSIONS: The outbreak of COVID-19 has required general surgery residency PDs to change numerous aspects of resident education and clinical roles. Future inquiry is needed to assess if these changes lead to appreciable differences in resident preparedness and career selection.